2015
DOI: 10.2174/2210289201506010010
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal Delivery Enhancement of Gel Containing Niosomes Loaded with Volvariella Volvacea Extract

Abstract: Our previous study demonstrated the potent in vitro collagen biosynthesis stimulating and antioxidant activities of Volvariella volvacea extract. This study was performed the loading of V. volvacea extract (VV) in niosomes (NV). The physicochemical characterization of the VV loaded niosomes and gel containing niosome of the extract (GNV) was studied. Rat skin transdermal absorption by Franz diffusion cells at 6 hours of NV, GNV was compared with V. Volvacea extract solution (SV). GNV and NV showed higher chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…8 illustrates that CUR niosomes, as well as ethosomes, gives rise to the highest amount of CUR retained or deposited in SC (120.6±10.31 µg/cm 2 ) for niosomes and (80.5±5.80 µg/cm 2 ) for ethosome among other formulations. Such finding revealed that niosomes and ethosomes are suitable for the penetration into the skin and localized as a depot, while gel system of lipid vesicles can deliver more drug to receiving compartment which represents for blood vessels 42 . Therefore, it is worthy to note that, the gel containing niosomes and ethosomes loaded with CUR appeared to be the most appropriate system for a topical anti-inflammatory application.…”
Section: Drug Release Kineticsmentioning
confidence: 96%
“…8 illustrates that CUR niosomes, as well as ethosomes, gives rise to the highest amount of CUR retained or deposited in SC (120.6±10.31 µg/cm 2 ) for niosomes and (80.5±5.80 µg/cm 2 ) for ethosome among other formulations. Such finding revealed that niosomes and ethosomes are suitable for the penetration into the skin and localized as a depot, while gel system of lipid vesicles can deliver more drug to receiving compartment which represents for blood vessels 42 . Therefore, it is worthy to note that, the gel containing niosomes and ethosomes loaded with CUR appeared to be the most appropriate system for a topical anti-inflammatory application.…”
Section: Drug Release Kineticsmentioning
confidence: 96%